Emergency demand, repeat and frequent presentations by older patients in metropolitan Melbourne: A retrospective cohort study using routinely collected hospital data. (18th January 2018) - Lowthian, Judy; Turner, Lyle; Joe, Angela; Pearce, Christopher; Brijnath, Bianca; Browning, Colette; Shearer, Marianne; Mazza, Danielle
Abstract: Objective: To describe patterns for potentially avoidable general practice (PAGP)‐type and non‐PAGP‐type ED presentations by older patients during 2008 and 2012. Methods: Retrospective analysis of ED presentations by patients ≥70 years for 2008 and 2012. Metropolitan Melbourne public hospital data were obtained from the Victorian Emergency Minimum Dataset. Outcomes were characteristics of PAGP‐type and non‐PAGP‐type presentations as defined by the Australian Institute of Health and Welfare; numbers and rates per 1000 population ≥70 years of repeat (×2–3/year) and frequent (≥ ×4/year) PAGP‐type and non‐PAGP‐type presentations. Results: The older metropolitan Melbourne population increased by 10.3% between 2008 and 2012, whereas the number of ED presentations increased by 12.7%. The volume of PAGP‐type presentations decreased by 2.6%, with declining rates per 1000 population ≥70 years of repeat (7.2–6.2) and frequent (0.7–0.4) presentation. In contrast, the volume of non‐PAGP‐type presentations grew by 15.4%, with increasing repeat (57.6–60.7) and frequent (13.1–14.2) presentation rates per 1000 population ≥70 years. The majority (39%) of non‐PAGP‐type presentations by frequent ED attenders were due to cardiovascular or respiratory problems. Conclusion: The rate of repeat and frequent PAGP‐type presentations by older people decreased in 2012 compared with 2008, suggesting that initiatives implemented to reduce avoidable presentations may have had an effect. However, an increase in the rate of frequent non‐PAGP‐type presentations, predominately for acute exacerbation of cardiovascular and respiratory conditions, has important implications for planning future healthcare delivery; hence, the importance of initiatives such as the Health Care Home.